2007
DOI: 10.1002/mop.22561
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism study of mechanical tuning in HTS filter application

Abstract: Mechanical tuning method using sapphire and copper rods for high temperature superconducting filters is presented. A three‐pole microstrip filter and a two‐pole patch filter were fabricated and tuned. Results show that the center frequency shifts toward lower end in dielectric tuning and toward either lower end or higher end in metallic tuning depending on the local electromagnetic field distribution.© 2007 Wiley Periodicals, Inc. Microwave Opt Technol Lett 49: 1565–1568, 2007; Published online in Wiley InterS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Dielectric rods can change the resonant frequency by changing the shunt capacitance to the ground [1]. To have a great influence on the resonant frequency, the rods are placed above the resonator where the electric field is concentrated.…”
Section: Tuning Of the Resonant Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…Dielectric rods can change the resonant frequency by changing the shunt capacitance to the ground [1]. To have a great influence on the resonant frequency, the rods are placed above the resonator where the electric field is concentrated.…”
Section: Tuning Of the Resonant Frequencymentioning
confidence: 99%
“…For wireless communication systems, HTS tuneable filters need wide-range tunability of the passband with remaining passband ripple. There are several reports on the center frequency tuneable HTS filters and trimming method for improving passband ripple of HTS filters [1]. H. Peng et al reported the trimming method which improves the passband ripple by adjusting the resonant frequency using dielectric and metallic screws [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Planar filters are more difficult to tune with tuning screws since the electric field tends to be trapped inside the dielectric. The use of tuning screws on planar filters is thus limited to fine tuning during production [17].…”
Section: Tunable Planar Filtersmentioning
confidence: 99%
“…To improve the HTS filter performance, many tuning methods have recently been developed . Researchers focus their attention on tuning center frequencies and fractional bandwidths of filters .…”
Section: Introductionmentioning
confidence: 99%